ISLAMIC ECO-SPIRITUALITY AND ENVIRONMENTAL CONSERVATION ACTION: A PHENOMENOLOGICAL STUDY OF ECOLOGICAL AWARENESS AMONG THE PEOPLE OF YOGYAKARTA - Lutfina Aribah; Sri Yati; Sembodo Ardi Widodo; Muhammad Wildan; Adiba Rifkiya (Universitas Nurul Jadid, 2026)
The global environmental crisis, in the form of waste, is particularly urgent in the city of Yogyakarta. This crisis stems from a weakening of ecological awareness and an anthropocentric view of society. This view places humans at the center of nature, leading to the exploitation of resources and severing spiritual ties with the environment. This study aims to explore how Islamic values shape and transform ecological awareness among the Muslim community in Yogyakarta, particularly in responding to the local waste crisis. The research uses a qualitative approach with a phenomenological type to explore the meaning of life experiences and spiritual awareness of the Muslim community in Wedomartani, Sleman, Yogyakarta. The research subjects consist of religious leaders and environmental activists who are active in religious value-based conservation activities. Data was collected through interviews, participatory observation, and documentation. The findings show that ecological awareness is formed through three dimensions: spiritual (viewing nature as verses of kauniyah), moral (internalization of the principles of an-nadhafatu minal iman and ihsan values), and social (sacred collective actions, such as community service that begins with prayer). This process of consciousness transformation goes through instrumental, reflective, and transcendental stages, where caring for the environment becomes an expression of worship (ubudiyah). Core Islamic values such as tauhid, amanah, ihsan, and syukur become the theological foundation that drives this transformation. Scientific contribution